Towards the Joint Study of Access Services and Universal Design for Learning - PATINIOTAKI, EMMANOUELA (International Journal of Language, Translation and Intercultural Communication, 2019)
Access services have been studied from various perspectives as types of Audiovisual Translation, including their role as tools for education, and foreign language learning in particular, when audiovisual material is used for learning purposes. This paper aims to introduce a research path in audiovisual accessibility, from an Audiovisual Translation point of view, and accessible education by joining the dots between Access Services and Universal Design for Learning, with the aim to propose a holistic approach to accessible learning environments. Within this context, both access services and Universal Design for Learning are seen as both functional and pedagogical tools that can be used to achieve education which satisfies the needs of all learners. The current contribution takes Subtitling for the D/deaf and the hard-of-hearing as an example of access services whose educational value has been established and investigates its potential role in an educational environment that has been based on the principles of Universal Design for Learning.